Financial Risks, Related Party Transactions and Value of BUMN Companies in Indonesia - Wijaya, Anggita Langgeng; Ratnasari, Ima Widha (Universitas Negeri Semarang, 2023)
Purpose : The research investigates the influence of financial risk on the value of state-owned companies (BUMN) on the Indonesia Stock Exchange with related party transactions as a moderating variable. Method : The population in this research is all state-owned companies listed on the Indonesia Stock Exchange from 2015 to 2022. The sample selection technique uses purposive sampling methods. Data analysis uses regression testing with moderating variables. Findings : The results of this research show that financial risk has a negative effect on the value of state-owned companies in Indonesia. Related party transactions (RPT) have a moderating effect that strengthens the influence of corporate financial risk on the value of BUMN companies. Novelty : The research can prove the role of related party transactions as a moderating variable on the influence of financial risk and the value of BUMN companies. Keywords : Company Value; Financial Risk; Related Party Transactions; Bankruptcy; BUMN